The Effectiveness of the Kana Kihon Complete Book for Learning of Hiragana Letters and Katakana for High School Students as the Initial Learners of Japanese Language - Mayasari, Erma Dewi; Roni, Roni; Nurhadi, Didik (International Journal for Educational and Vocational Studies, 2020)
Language skills that must be mastered in language are listening, speaking, reading and writing. Japanese language learning specifically kana letters in the 2013 curriculum is not discussed in detail in the main complementary books like the books in the previous curriculum. The kana kihon supplementary book is the result of a research development product that has gone through the process of assessing the quality of a book, both from the validation assessment, the level of practicality and effectiveness. Effectiveness Complementary textbook learning can be seen from observing the activities of teachers, students and completeness of learning outcomes. From the results of the Kana Kihon book research effectively used with the following details, namely, 1) based on student activities obtained a percentage of 81.99%, 2) based on teacher activity obtained a percentage of 81.93%, and 3) based on the results of completeness learning effectively used with the level the percentage of 83.78%. With a good category of the three percentages, the kihon kana book is effectively used in learning hiragana letters and katakana (kana) for high school students as early learners of Japanese. The supplementary letter kana for students in class X of SMA / MA certainly has advantages and disadvantages. Therefore, teachers should be developed, especially Japanese language teachers so that they do not refer to existing text books so teachers need to be more productive in developing books that are appropriate for their students.